One-Year Incidence Rate of Injuries among Primary School Pupils in an Iranian Community - R Vazirinejad; A Esmaeili; A Sarsangi; M Kazemi; JM Lilley (Tehran University of Medical Sciences, 2007)
Background: To describe the risk and the patterns of injuries taken place inside the primary schools among pupils in an Iranian community. Methods: A total population of 11,543 pupils were followed and all injuries were recorded. Information about age, gender, deprivation, time, day and month of injuries, cause and the outcome of injuries were collected using a checklist. Results: One hundred and twenty five cases were reported giving an overall one-year incidence rate of 10.8 per 1000 person-years-at-risk. Overall incidence rate of injuries among boys was significantly greater than this incidence rate among girls (Relative Risk =1.6, 95% CI= 1.1 - 2.2). The greatest incidence rate was reported among year five pupils in both genders (18.6 per 1000 boys and 13.2 per 1000 girls). "Fall" was the most common cause of injuries followed by "hit by objects". Majority of injuries were "cured without rest" and only seven pupils were admitted in hospital. Conclusion: The level of risk calculated in this survey could be used in programs aiming to prevent injuries in primary schools and a nationwide surveillance system in the country is recommended.